Urgency for surgical evacuation of post traumatic Intracranial acute epidural hematoma - GP Mishra; Najm us Saqib; Azmat Ali; Mohammad Hashim Awad; Syed Osama Mehboob (International Journal of Medical Research and Review, 2015)
Introduction: Intracranial epidural haematoma, (EDH) is a collection of blood between the skull and dura mater due to head injury. It is considered to be the most serious complication of head injury requiring immediate diagnosis and surgical intervention.Background: The aim of our study was to present the outcome of consecutive patients with Acute EDH managed surgically & to prove the high risk of death or permanent brain damage without prompt surgical intervention.Method: In this study we retrospectively examined all consecutive head injury cases managed between September 2014 & September 2015 and diagnosed with acute traumatic epidural hematoma in isolation or in combination with intra cranial lesions. Age, sex, mechanism of injury, time of presentation, Glasgow Coma Score (GCS), pupil reactivity, time of surgery and clinical outcomes were evaluated.Results: Out of 31 cases 87%, (n=27) were males and 13 %,( n=4) were females. The mean age was 17.75 years. 74% (n=23) patients under the age of 25years. The most common mode of injury was road traffic accident 48%, (n=15) followed by fall 42%, (n=13). The mortality rate was 6% (n=2). The time interval between trauma & operation of both patients who died were more than 8 hours.Conclusions: An acute epidural hematoma is an emergency condition, the diagnosis of the EDH must be promptly made by CT scan and the patient should be immediately transferred into a neurosurgical centre, Early surgical intervention is associated with the best outcome.